Poly(ethylene glycol) or poly(2-ethyl-2-oxazoline) – A systematic comparison of PLGA nanoparticles from the bottom up - Dirauf, Michael; Grune, Christian; Weber, Christine; Schubert, Ulrich S.; Fischer, Dagmar (European Polymer Journal, 2020)
In times of drastically increasing numbers of scientific reports dealing with the drawbacks of poly(ethylene glycol) (PEG), the search of PEG alternatives has never been more urgent. This study describes a one–to–one comparison of poly(2-ethyl-2-oxazoline)-b-poly(lactic-co-glycolic acid) (PEtOx-b-PLGA) to commercial PEG-b-PLGA from the bottom up in order to verify the similarity of both polymer classes when applied in nanoparticle formulation processes. For this purpose, a library of block copolymers with molar masses (Mn) ranging from 6500 to 60,000 g mol−1 was synthesized via tin-(II)-ethyl hexanoate (SnOct2) catalyzed ring-opening polymerization (ROP) of lactide and glycolide utilizing PEtOx-OH as a macroinitiator in the melt. The PEtOx-b-PLGA polymers were adjusted in terms of molar mass, dispersity and lactide to glycolide ratio of the PLGA block. Nanoparticle formulations showed a similar behavior for both polymer libraries. Zeta potentials as well as hydrodynamic diameter measured by laser light scattering were in excellent agreement, demonstrating the eligibility of PEtOx-b-PLGA as an alternative to formulate “stealth” nanoparticles.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Block copolymer; Nanoparticle; PLGA; Poly(2-oxazoline); Poly(ethylene glycol); Polyester